Need of Export Promotion Organizations in Emergent India: The Boost for a Growing Economy - Gupta, Prateek (Journal of Commerce and Trade, 2007)
The development of a country is always depended on its economical structure & conditions. If economic condition of a country is healthier, the development will also be in a nice growth. The economic condition of a country always depends on its national and international tread. Export is a very useful instrument to boost economy of a country. To stand with other competitors abroad, it is necessary to promote the export. From the past achievements and huge growth in economical condition, it is evident that export promotion should be regarded as a crucial tool of development. It is not an easy task for an individual or any firm to promote export. The basic reason behind it is the different nature, taste and living standard of each country. Export Promotion Organizations are playing a vital role in this field. These Councils are dedicated to boost exports from India and assist the member exporters through the various promotional activities. Hence, role of export promotion organizations has been focused in this paper.